2022
DOI: 10.3389/fpubh.2022.822741
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Use Type, Fear of Missing Out, Social Support, and Smartphone Screen Time Among Adolescents in Korea: Interactive Effects

Abstract: This study aims to examine the relationship between intrapersonal factors, interpersonal factors, smartphone screen time, and the moderating roles of interpersonal factors, on the basis of the ecological model. This study is a cross-sectional and descriptive study. A total of 428 participants from four public middle schools were selected through convenience sampling (55.1% female; Mean age 13.0 ± 0.78). Data were collected through self-report questionnaires that contained questions about sociodemographic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Social support from parents and family but also from friends and peers is closely associated with problematic smartphone use in adolescents and young adults [ 64 ]. Other authors who researched PMPU and analyzed its relationship with perceived social support, with the same study tool as the following study, obtained similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Social support from parents and family but also from friends and peers is closely associated with problematic smartphone use in adolescents and young adults [ 64 ]. Other authors who researched PMPU and analyzed its relationship with perceived social support, with the same study tool as the following study, obtained similar results.…”
Section: Discussionmentioning
confidence: 99%
“…In short, as parents' overdependence on smartphones results in failure to provide emotional support and basic safety for their children ( 57 ), adolescents tend to become cognitively and behaviorally vulnerable in human relationships ( 58 ). This eventually hinders building healthy relationships with their family and friends, making them show aggressive behaviors, and ultimately deteriorating their existing relationships with family and friends, which leads to greater dependence on their smartphones ( 12 ). Parental smartphone addiction and aggression showed a very weak relationship in this study, however, as aggression is a key variable of adolescents' smartphone dependence, there must be repeated studies on the subject in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that parental factors, one of the environments surrounding adolescents, affect their smartphone use both directly and indirectly, emphasizing the importance of family roles (9)(10)(11)(12). Specifically, parents as role models play a critical role in adolescents' problematic behaviors (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found high social support to be associated with lower trait-FoMO. 35,36 ASMU, Trait-FoMO, and State-FoMO…”
mentioning
confidence: 99%
“…Previous research has demonstrated that good interpersonal relationships and higher friend support are protective factors for trait-FoMO. 35,36,42 Hence, it can be inferred that ASMU may be associated with a reduction in trait-FoMO. In addition, ASMU is shown to be linked to satisfied need to belong, 43 reduced loneliness and depression, 41 and increased life satisfaction and selfesteem.…”
mentioning
confidence: 99%